PERANAN SULINGGIH DALAM MENINGKATKAN SRADDHA DAN BHAKTI UMAT HINDU BALI - I Kadek Sukadana; Pradna Lagatama (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The current era of globalization has brought various impacts on the world community. This also has an impact on the religious life of Balinese Hindus. Currently, Balinese Hindus are challenged by themselves and by other people to provide answers to questions regarding the implementation of their religion. Conditions like this require anticipatory steps so that the joints of identity of Balinese Hindus are not porous due to the shocks of globalization. This is where serious attention is needed from religious leaders and high religious institutions who would be able to give love and faith (Sraddha and Bhakti) to Balinese Hindus in religious teachings, by providing guidance and understanding about religious teachings. The study is a qualitative study, with the data collection method is a literature study, namely the focus of collecting data from various literatures that are relevant to the research topic. While the data analysis technique used is descriptive narrative analysis technique to analyze and present information in this study. In this paper, it is known that Sulinggih has an honorable position in society in accordance with the swadharma and sesana kawikon he adheres to as already exists in religious literature such as Shiva Sesana, Manawa Dharmasastra and so on. Sulinggih plays an important role in increasing sraddha and devotional service for Balinese Hindus, namely as a leader and guide for the people in accordance with Sulinggih's dharma, as a pemmuput or leader of the ceremony, as a driver for increasing sraddha and devotional service through Sulinggih activities providing Dharma Discourse, Dharma Tula, Dharma Sadhana, Dharma Yatra. Dharma Gita and other regular flute activities that can be used as role models. Keywords: Role of Sulinggih; Sraddha and Bhakti; Balinese Hindus